Faunal Analysis of the Early Modern Bishop's Farm at Skalholt, Arnessysla Iceland - McGovern, Thomas (NABO and CUNY) (the Digital Archaeological Record)
This dissertation presents the analysis of faunal material recovered from middens outside the main complex of the Bishop of Southern Iceland´s Cathedral farm at Skálholt, Arnessysla, Iceland. Issues of diet, deposition patterns, as well as participation in larger trade and intellectual networks addressed. All of these issues are examined in order to investigate larger issues centered around the early modern Atlantic world. The Skálholt material is also compared with the larger body of existing early modern Icelandic archaeofaunal data in order to investigate issues of adaptation and resilience in the face of harsh climatic as well as social and economic conditions.